EVALUATION OF LIVING HIERARCHICAL TELECOMMUNICATION NETWORKS OF MILITARY PURPOSE - Leonid A. Bondarenko; Nikolay A. Mаsesov; Kateryna A. Efanova; Oleg I. Sadykov (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
One of the most demanded and loud problems in telecommunication networks is the development of methodological bases for evaluating the survivability of hierarchical telecommunication systems when they are destroyed and restored. The article reflects the views of the authors on the introduction into practice of the work of the management bodies of the communication of the performance of calculations of functional characteristics, which allow to determine the quality of the communication system. Also, one of the promising methods of a staff model for calculating the survivability of a communication system based on the calculations of system connectivity indicators is proposed, which will solve the problem of ensuring the survivability of telecommunication networks, which is also related to the reliability and accuracy of the information transmitted, the number of possible network reconfigurations, as well as the ability to continue functioning of the network in the event of destruction.